An investigation of chromium and nickel uptake in tomato plants irrigated with treated waste water at the Glen Valley farm, Gaborone, Botswana - Schoeman, J.J. (Jakob Johannes) (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2011.